Improving FOSS photogrammetric workflows for processing large image datasets - Martinez-Rubi, O. (2020)
In the last decade Photogrammetry has shown to be a valid alternative to LiDAR techniques for the generation of dense pointclouds in many applications. However, dealing with large image sets is computationally demanding. It requires high performance hardware and often long processing times that makes the photogrammetric pointcloud generation not suitable for mapping purposes at regional and national scale. These limitations are partially overcome by commercial solutions, thanks to the use of expensive and dedicated hardware. Nonetheless, a Free and Open-Source Software (FOSS) photogram metric solution able to cope with these limitation s is still missing.